Political Polarization and Islamic Identity among Indonesian Muslims: A Socio-Political Analysis of Digital Religious Communities - M. Rizal Qosim (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the relationship between political polarization and the construction of Islamic identity among Indonesian Muslims within the context of digital religious communities. The rapid development of digital communication technologies and social media platforms has significantly transformed patterns of religious interaction, political participation, and identity formation in contemporary Muslim societies. Digital religious communities have emerged as influential spaces where religious interpretations, political narratives, and ideological preferences are continuously negotiated and disseminated. This research aims to analyze how political polarization shapes the formation and expression of Islamic identity in online communities and how digital environments contribute to reinforcing or transforming socio-political attitudes among Indonesian Muslims. Using a socio-political approach, this study explores the interaction between religious discourse, political affiliation, and digital engagement within virtual communities. The analysis suggests that digital religious spaces function not only as platforms for religious expression but also as arenas of political contestation that may intensify ideological divisions and strengthen group-based identities. At the same time, these platforms provide opportunities for dialogue, participation, and the emergence of new forms of religious and political engagement. The study contributes to contemporary discussions on Islam, politics, and digital society by highlighting the evolving relationship between religious identity and political dynamics in Indonesia's increasingly interconnected digital landscape.